SHS of Silicon‐Based Ceramics for the High‐Temperature Applications. Issue 8 (29th May 2018) - Vorotilo, Stepan; Potanin, Artem Y.; Iatsyuk, Ivan V.; Levashov, Evgeny A.
Abstract : High‐temperature materials attract a growing interest from both the scientists and engineers, since the increase of the operating temperatures is crucial for the enhancement of many energy conversion processes. Another area of application of high‐temperature materials is high‐velocity air flight, where the ultra‐high temperature ceramics (UHTCs) are pivotal for the creation of robust nose tips and leading edges of the skins of high‐velocity jets. Compounds of refractory metals with silicon, such as TaSi2, MoSi2, ZrSi2, are characterized by unrivaled resistance in aggressive environments. However, most of them are not suitable for application as high‐temperature structural materials due to the low mechanical properties. Therefore, they are frequently used as a constituent for the high‐temperature composite materials such as TaSi2 –SiC, ZrC–MoSi2, ZrB2 –MoSi2, ZrB2 –ZrSi2 . One of the most convenient ways of producing these composite materials is self‐propagating high‐temperature synthesis (SHS), known for its high productivity, energy‐efficiency, and ecological safety. This review summarizes the latest developments of the SHS of the silicon‐based high‐temperature ceramics. Abstract : This review summarizes the available data concerning the microkinetic features, structure, and phase formation mechanisms during the SHS of high‐temperature composites in Mo–Si–B, Mo–Si–B–C, Ta–Si–C, Zr–Si–B, Zr–Si–B–C, and Zr–Si–B–Al systems, as well as the mechanical properties and oxidation resistance of SHS products both as bulk ceramics and as coatings. As the figure shows, SHS is a simple, fast, and facile method of synthesis of high‐temperature ceramics and is well‐suited for the large‐scale production.